2018
DOI: 10.3390/w10111600
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution Characteristics of Rainfall for Two-Jet Collisions in Air

Abstract: Many researchers have studied the energy dissipation characteristics of two-jet collisions in air, but few have studied the related spatial rainfall distribution characteristics. In this paper, in combination with a model experiment and theoretical study, the spatial distributions of rainfall intensity of two-jet collisions, with different collision angles and flow ratios, are systematically studied. The experimental results indicated that a larger collision angle corresponds to a larger rainfall intensity dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Meanwhile, a higher inflow discharge can lead to a stronger enhancement effect of low ambient pressure on the average rain amount with the growth rate from sharp to stable. In addition, the atomized source ratio is within ((0~30) × 10 −3 )% according to Equation (6), which matches the same trend of average rain amount affected by low ambient pressure.…”
Section: Analysis Of Depressurized Effectssupporting
confidence: 67%
See 1 more Smart Citation
“…Meanwhile, a higher inflow discharge can lead to a stronger enhancement effect of low ambient pressure on the average rain amount with the growth rate from sharp to stable. In addition, the atomized source ratio is within ((0~30) × 10 −3 )% according to Equation (6), which matches the same trend of average rain amount affected by low ambient pressure.…”
Section: Analysis Of Depressurized Effectssupporting
confidence: 67%
“…In surveying global studies on atomized flow, it is found that most flood discharge atomization occurs in China, especially for hydropower stations with ski-jump energy dissipation characterized by high heads, high discharge and deep canyons. It has been widely recognized that hazard sources arise from strong atomized rain, and major atomized rain sources are generated by aerial waterjet collisions and the hydraulic impact of falling waterjets into a water cushion [6]. With approximately 30 years of progressive research, the damages caused by strong atomized rain have been greatly reduced, but they still occur occasionally, such as the severe landslides at the Longyangxia Hydropower Station in 1987 and 1989 due to its soft geology and arid climate [7], the unexpectedly high level of atomized rain at the Ertan Hydropower Station due to a high energy dissipation ratio with aerial waterjet collisions in 1998 [8], the rare rainstorm disaster of the Shuibuya Hydropower Station formed by the combination of atomized and natural rain in 2016 [9], and the flood at the Nazixia Hydropower Station Powerhouse due to unreasonable design in 2017 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Both physical model tests and theoretical analyses have demonstrated that the distributions of the intensity of the rainfall atomized from two jets when they collide in air and when they do not collide in air differ significantly and that the impingement angle and flow-rate ratio of the two jets significantly affect the distribution of the intensity of the rainfall formed from their spallation after the collision in air (Yuan et al 2018). Studying the effects of collision on the spallation trajectories of jets as well as the distributions of the characteristic values of several parameters (size, velocity, and quantity) of water droplets during the collision and spallation processes of jets from a mesoscale perspective can facilitate an in-depth understanding of the FDA pattern when jets collide in air.…”
Section: Jet Collision In Airmentioning
confidence: 99%
“…Figure 9 shows the correction point coordinate trajectories of three cases (30 s, 300 frames), which are also on behalf of UAV drift trajectories. The UAV drift trajectories present obvious randomness under the influence of UAV hover stabilization precision, operator control skill and external environment, e.g., atomization wind that is caused by flooding flow splitting and energy dissipation [30]. Table 1 shows the statistical parameters of UAV offset displacements of three cases, i.e., the average offset displacement and max offset displacement.…”
Section: Application Assessment Of Uavi-fmwlmentioning
confidence: 99%